SURVEI SARANA DAN PRASARANA PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SEKOLAH LUAR BIASA NEGERI KENDAL DAN SEKOLAH LUAR BIASA ABC SWADAYA DI KABUPATEN KENDAL (Department of Physical Education, Sport, Health and Recreation, 2014)
Research purposes to determine the availability of sports facilities and infrastructure on physical education and health in sport SLB Kendal. Types of research used in this study is a qualitative research method survei.Populasi used in this study is comprised two schools, namely SLB SLB ABC Domestic Non Kendal and Kendal. Methods of data collection using observation, documentation, and interviews. Analysis using descriptive analysis techniques percentage. Results of research in the School of Foreign Extraordinary Kendal produce availability sarpras by 389.9% 0.9% larger than ABC SLB